FOREWORD - Monai KRAIRIKSH; Jiro HIROKAWA (My University, 2019)
on Antennas and Propagation (EurAAP), Institute of Antenna Engineers of Taiwan, Korea Institute of Electronics Engineers (KIEES), and Radio and Electronics Association of Vietnam (REV).ISAP2017 attracted 452 submissions from 33 countries.With the careful review, 411 papers were accepted from 28 countries
Keywords: null